Influences of Different Preparation Conditions on Catalytic Activity of Ag2O-Co3O4/γ-Al2O3 for Hydrogenation of Coal Pyrolysis - Zhang, Lei; Xiang-ling, Sha; Zhang, Lei; Rui, Wang; Lixin, Zhang; Xinqian, Shu (Journal of Spectroscopy, 2014)
A series of catalysts of Ag2O-Co3O4/γ-Al2O3 was prepared by equivalent volume impregnation method. The effects of the metal loading, calcination time, and calcination temperatures of Ag and Co, respectively, on the catalytic activity were investigated. The optimum preparing condition of Ag2O-Co3O4/γ-Al2O3 was decided, and then the influence of different preparation conditions on catalytic activity of Ag2O-Co3O4/γ-Al2O3 was analyzed. The results showed the following: (1) at the same preparation condition, when silver loading was 8%, the Ag2O-Co3O4/γ-Al2O3 showed higher catalyst activity, (2) the catalyst activity had obviously improved when the cobalt loading was 8%, while it was weaker at loadings 5% and 10%, (3) the catalyst activity was influenced by different calcination temperatures of silver, but the influences were not marked, (4) the catalyst activity can be influenced by calcination time of silver, (5) different calcination times of cobalt can also influence the catalyst activity of Ag2O-Co3O4/γ-Al2O3, and (6) the best preparation conditions of the Ag2O-Co3O4/γ-Al2O3 were silver loading of 8%, calcination temperature of silver of 450°C, and calcinations time of silver of 4 h, while at the same time the cobalt loading was 8%, the calcination temperature of cobalt was 450°C, and calcination time of cobalt was 4 h.